PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis sp.) YANG DIPELIHARA PADA MEDIA BERSALINITAS - Aliyas, Aliyas (JSTT, 2016)
Tilapia has a high tolerance to salinity waters. This study aims to assess the growth and survival of tilapia reared at salinity. Assessing the optimal salinity for the growth and survival of tilapia fish. This study will use a completely randomized design (CRD). Completely randomized design to be used consists of 4 levels of treatment with each of 4 replicates ie Treatment A: Maintenance of tilapia in medium salinity 0 ppt, Treatment B: Maintenance of tilapia in the media with a salinity of 10 ppt, Treatment C: Maintenance fish indigo in media with 20 ppt salinity, treatment D: Maintenance of tilapia in media with 30 ppt salinity The variables measured were daily growth rate and survival of tilapia reared at salinity media The results showed that the growth of tilapia is affected by salinity, The highest absolute growth value was obtained at a salinity of 20 ppt with an average of 2.68 grams, then followed at a salinity of 30 ppt with an average of 2.35 grams and a salinity of 10 ppt with an average of 2.31 grams and the best growth rate achieved at a salinity of 20 ppt is 26,48%. Tilapia fish survival was not significantly different in the four treatments. This suggests that the increase in salinity from 0 ppt - 30 ppt does not affect the survival of tilapia fish